Platinum‐induced peripheral neurotoxicity: From pathogenesis to treatment. (24th October 2019) - Staff, Nathan P.; Cavaletti, Guido; Islam, Badrul; Lustberg, Maryam; Psimaras, Dimitri; Tamburin, Stefano
Abstract: Platinum‐induced peripheral neurotoxicity (PIPN) is a common side effect of platinum‐based chemotherapy that may cause dose reduction and discontinuation, with oxaliplatin being more neurotoxic. PIPN includes acute neurotoxicity restricted to oxaliplatin, and chronic non‐length‐dependent sensory neuronopathy with positive and negative sensory symptoms and neuropathic pain in both upper and lower limbs. Chronic sensory axonal neuropathy manifesting as stocking‐and‐glove distribution is also frequent. Worsening of neuropathic symptoms after completing the last chemotherapy course may occur. Motor and autonomic involvement is uncommon. Ototoxicity is frequent in children and more commonly to cisplatin. Platinum‐based compounds result in more prolonged neuropathic symptoms in comparison to other chemotherapy agents. Patient reported outcomes questionnaires, clinical evaluation and instrumental tools offer complementary information in PIPN. Electrodiagnostic features include diffusely reduced/abolished sensory action potentials, in keeping with a sensory neuronopathy. PIPN is dependent on cumulative dose but there is a large variability in its occurrence. The search for additional risk factors for PIPN has thus far yielded no consistent findings. There are currently no neuroprotective strategies to reduce the risk of PIPN, and symptomatic treatment is limited to duloxetine that was found effective in a single phase III intervention study. This review critically examines the pathogenesis, incidence, risk factors (both clinical and pharmacogenetic), clinical phenotype and management of PIPN.